2020
DOI: 10.1017/s0031182020000931
|View full text |Cite
|
Sign up to set email alerts
|

Light intensity and spectral distribution affect chytrid infection of cyanobacteriaviamodulation of host fitness

Abstract: Abstract Light gradients are an inherent feature in aquatic ecosystems and play a key role in shaping the biology of phytoplankton. Parasitism by chytrid fungi is gaining increasing attention as a major control agent of phytoplankton due to its previously overlooked ubiquity, and profound ecological and evolutionary consequences. Despite this interest, if and how light conditions modulate phytoplankton chytridiomycosis remains poorly studied. We investigated life-history tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 49 publications
(75 reference statements)
0
19
0
Order By: Relevance
“…While we did not measure it directly here, predation by zooplankton could have also been important as shown by Jacquet et al (2014) some situations (i.e., low growth, size reduction, toxin absence or weak concentrations), impact P. rubescens significantly (Oberhaus et al, 2007;Perga et al, 2013;Jacquet et al, 2014). An increased vulnerability to parasites such as viruses or chytrids (Tao et al, 2020) could also be proposed although it remains to be tested. After 2018, the lack of an inoculum, and a sunshine average particularly low prevented P. rubescens to develop again.…”
Section: Discussionmentioning
confidence: 99%
“…While we did not measure it directly here, predation by zooplankton could have also been important as shown by Jacquet et al (2014) some situations (i.e., low growth, size reduction, toxin absence or weak concentrations), impact P. rubescens significantly (Oberhaus et al, 2007;Perga et al, 2013;Jacquet et al, 2014). An increased vulnerability to parasites such as viruses or chytrids (Tao et al, 2020) could also be proposed although it remains to be tested. After 2018, the lack of an inoculum, and a sunshine average particularly low prevented P. rubescens to develop again.…”
Section: Discussionmentioning
confidence: 99%
“…The term 'refuge' in this case does not indicate a physical location but instead a set of environmental conditions that prevents chytrid infection. A recent study has shown that increasing the quantity and quality of light increases chytrid infection of P. rubescens (Tao et al, 2020). Because of the vertical position of P. rubescens in the lake, it is typically subjected to relatively large variations in temperature and light across the steep environmental gradients in its metalimnetic population.…”
Section: Introductionmentioning
confidence: 99%
“…It is typically found in the metalimnion of deep stratifying lakes, and is adapted to lower light and temperature conditions than other cyanobacteria (Legnani et al, 2005; Walsby et al, 2004). (Bruning, 1991a; Rohrlack et al, 2015; Tao et al, 2020). P. rubescens has a very efficient light harvesting complex composed of both phycocyanin and phycoerythrin in addition to chlorophyll, which allows it to continue photosynthesis at light levels below that of many other phytoplankton species (Davis & Walsby, 2002; Oberhaus et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Some research focussed on altered predator-prey interactions by fungal infections of cyanobacterial blooms (e.g. Kagami et al 2007, Tao et al 2020. Agha et al (2016) focussed on chytrid infection of cyanobacterial populations, revealing a positive impact on the zooplankter Daphnia by improving food quality.…”
Section: Introductionmentioning
confidence: 99%